Assessment of potential greenhouse gas mitigation of available household solid waste treatment technologies - Hoang Minh Giang; guyen Duc Luong; Luong Thi Mai Huong (Waste Technology, 2013)
Current household solid waste treatment practices in most cities in Vietnam caused a great amount of direct greenhouse gas (GHG) emissions. Available solid waste treatment technologies should be seriously taken  into consideration as a wedge of GHG mitigation in waste sector base on presently Vietnamese economic conditions. This study aim to evaluate the potential amount of GHG mitigation from current domestic solid waste treatment technologies in Vietnam including landfills and composting from various management scenarios. In oder to use Tier 2 model of IPCC 2006 for GHG estimation from landfills, an analysis on current household solid waste management system of the city was obtained by using material flow analysis approach. A case study in Hanoi, the capital city of Vietnam was carried out in this research. As a result, there was a reduced of over 70% of the amount of CH4 emissions and  up to 53% of total GHG saving (CO2-eq) from avoiding organic waste to landfill. In addition, applying an energy recovery from LFG system to available landfills would lead to aproximately 75% of GHG saved compare to current emission of waste sector.Doi: http://dx.doi.org/10.12777/wastech.1.1.10-16Citation: Giang, H.M.,Luong, N.D., and Huong, L.T.M.2013. Assessment of potential greenhouse gas mitigation of available household solid waste treatment technologies. . Waste Technology 1(1):6-9. Doi: http://dx.doi.org/10.12777/wastech.1.1.10-16